Chemical and structural analyses of the graphene nanosheet/alumina ceramic interfacial region in rapidly consolidated ceramic nanocomposites. (February 2018) - Ahmad, Iftikhar; Islam, Mohammad; Alharthi, Nabeel H; Alawadhi, Hussain; Subhani, Tayyab; Munir, Khurram S; Shah, Syed Ismat; Inam, Fawad; Zhu, Yanqiu
Graphene nanosheets (GNS) reinforced Al2 O3 nanocomposites were prepared by a rapid sintering route. The microhardness and fracture toughness values of the resulting nanocomposites simultaneously increased due to efficient graphene nanosheet incorporation and chemical interaction with the Al2 O3 matrix grains. The properties enhancement is attributed to uniformly dispersed graphene nanosheet in the consolidated structure promoted by high surface roughness and ability of graphene nanosheet to decorate Al2 O3 nanoparticles, strong GNS/Al2 O3 chemical interaction during colloidal mixing and pullout/crack bridging toughening mechanisms during mechanical testing. The GNS/Al2 O3 interaction during different processing stages was thoroughly examined by thermal and structural investigation of the interfacial area. We report formation of an intermediate aluminum oxycarbide phase via a confined carbothermal reduction reaction at the GNS/Al2 O3 interface. The graphene nanosheet surface roughness improves GNS/Al2 O3 mechanical attachment and chemical compatibility. The Al2 O3 /GNS interface phase facilitates efficient load transfer, thus delaying failure through impediment of crack propagation. The resulting nanocomposites, therefore, offer superior toughness.